THE INFLUENCE OF BRAND AWARENESS, PERCEIVED QUALITY, BRAND ASSOCIATIONS, AND BRAND LOYALTY ON THE BRAND EQUITY OF OPPO SMARTPHONES - Suwiryo, Febi Sugianto; Aryandha, Pradita Nindya (Business Management Analysis Journal (BMAJ), 2024)
Brand equity is a set of assets and values associated with a brand. Several factors influence it, namely brand awareness, perceived quality, brand associations, and brand loyalty. This research is expected to provide insight to understand the influence of brand awareness, perceived quality, brand associations, and brand loyalty on the brand equity of Oppo smartphones. This research used purposive sampling as the sampling method, the questionnaire as the data collection method, and distributed to 145 students of the Faculty of Business, PGRI University of Yogyakarta. The data were evaluated using validity and reliability tests and analyzed with partial, simultaneous, and multiple linear regression tests. Partial positive impact is shown by brand awareness, brand association, and brand loyalty on brand equity. However, perceived quality has a negative effect on brand equity. The simultaneous impact is shown by brand awareness, perceived quality, brand association, and brand loyalty on the brand equity of the Oppo smartphone. However, this research has a small sample size and limited variables used; future research is expected to expand the sample size and include new variables.